"Post”-pandemic entrepreneurs: contribution to innovation management - Mota, Teresa Lenice Nogueira da Gama; Galdino, Sarah Monteiro; Grangeiro Filho, José Wellington Alves; Martins, Quitéria Livia Farias; Leal, Francisco Davi Pinheiro (Revista de Administração da UFSM, 2022)
Objective - This research’s aim was to understand the practice of innovative management in the retail trade of the city of Sobral, Ceará, so as to provide a contribution to such enterprises’ sustainability, representing more than 50% of the municipality’s GDP and which have been suffering the consequences of the COVID-19 pandemic, as well as stimulating new research fronts for the retail trade’s areas of innovation. Design / methodology / approach - A field investigation was carried out through unidentified respondents by using a semi-structured questionnaire and working with theoretical creativity categories, innovation and knowledge management, so as to analyze the innovative management process. This work made use of the qualitative method with descriptive goals, and the analysis of data was done by narrative synthesis means. Results - The results show that there is already a favorable climate for innovation management in the retail trade business segment of Sobral. However, it is observed that it is necessary to organize the segment governance and stimulate creativity and knowledge management as innovation factors. Technology transfer, through the university-business partnership, will need to be induced for the impacts and competitive transformations for the sector to be completed. Originality / value - The research is considered relevant since the theme of innovation management in retail trade is relatively new in the scientific area, seeing that it is able to guide future research in other municipalities, as well as deepening the elements which enable a university-company approach such as the competitiveness factor which constitute the main limitations of this work.